Measuring Deliberation within Indonesia’s Representative Institutions: ARoadmap for Public Aspiration Management by the MPR RI - Mohammad Reza; Indah Kusuma Wardhani (Pelopor Publikasi Akademika, 2026)
This article examines the compatibility of implementing deliberative democracy in Indonesia through a comparative constitutional analysis that draws on normative-juridical and empirical-comparative studies, positioning deliberative democracy as the main analytical framework while critically engaging with Mouffe's agonistic perspective and Dryzek's discursive perspective. This article analyzes the gap between the ideal of deliberation and the institutional reality of the MPR, DPR, and DPD as representative institutions in Indonesia. Comparative studies with models from Ireland, Germany, and Nordic countries are guided by the strict tertium comparation is criteria regarding the level of institutionalization of deliberation, the mechanism of coupling with legislative institutions, and the capacity to produce legitimate policy outputs. The findings indicate that Indonesia has significant deliberative cultural roots through deliberation and consensus, but these cultural values contain internal tensions that have the potential to hinder authentic deliberation if not carefully designed. Based on this analysis, this article proposes a roadmap for managing public aspirations by the People’s Consultative Assembly (MPR RI), which includes regulatory reform, institutional repositioning, the development of ideal mechanisms, and the anticipation of potential challenges, while also accounting for the inherent risk of elite capture within deliberative institutional frameworks.